2012
DOI: 10.1186/1743-7075-9-66
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of Key L-Carnitine Homeostasis Mechanisms during Postnatal Development in Rat

Abstract: BackgroundThe conditionally essential nutrient, L-carnitine, plays a critical role in a number of physiological processes vital to normal neonatal growth and development. We conducted a systematic evaluation of the developmental changes in key L-carnitine homeostasis mechanisms in the postnatal rat to better understand the interrelationship between these pathways and their correlation to ontogenic changes in L-carnitine levels during postnatal development.MethodsmRNA expression of heart, kidney and intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…Analysis of liver enzyme activity in the present study indicated that GK activity was also increased following PCE 50 treatment, by 37% as compared to the DC group (data not shown). Acyl-Coenzyme A oxidase 1 (ACOX1) and carnitine acetyltransferase (Cpt) are important proteins involved in fatty acid β-oxidation [ 23 , 24 , 25 , 26 , 27 ] and acyl-CoA synthetase long-chain family member 5 (ACSL5) is involved in lipogenesis [ 28 , 29 ]. Microarray analysis identified 2 genes with increased liver expression levels and 3 genes with altered adipose expression in PCE-treated db/db mice ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of liver enzyme activity in the present study indicated that GK activity was also increased following PCE 50 treatment, by 37% as compared to the DC group (data not shown). Acyl-Coenzyme A oxidase 1 (ACOX1) and carnitine acetyltransferase (Cpt) are important proteins involved in fatty acid β-oxidation [ 23 , 24 , 25 , 26 , 27 ] and acyl-CoA synthetase long-chain family member 5 (ACSL5) is involved in lipogenesis [ 28 , 29 ]. Microarray analysis identified 2 genes with increased liver expression levels and 3 genes with altered adipose expression in PCE-treated db/db mice ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heart M-CPT1 enzyme activities were measured as reported by Ling et al [ 29 ] with some modifications. Frozen tissue was homogenized in buffer (20 mM HEPES pH 7.4, 140 mM KCl, 10 mM EDTA and 5 mM MgCl 2 ) and after centrifugation; the mitochondrial pellet was resuspended in a homogenization buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Total CPT activity was determined spectrophotometrically according to the method of Ling et al [21]. Briefly, aliquot of the liver homogenate equivalent to 20 μg protein was mixed in 200 μL of reaction buffer containing 20 mM HEPES, 1 mM EGTA, 220 mM sucrose, 40 mM KCl, 0.1 mM 5,5ʹ-dithio-bis (2-nitrobenzoic acid), 1.3 mg/mL BSA, and 40 μM palmitoyl-CoA, pH 7.4.…”
Section: Determination Of Hepatic Carnitine Palmitoyl Transferase (Cpmentioning
confidence: 99%